Strategic Management Accounting: Legal Aspects and Practical Significance - NAZAROVA, Vera; SHTILLER, Marina; SELEZNEVA, Irina; KOHUT, Oksana; DAUZOVA, Aida (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The article considers the issues of substantiation and development of strategic management accounting model focused on the British-American concept. Management accounting is to give top management answers to the questions about real income and real expenses of their business, about the amount of actually earned profit, on total assets of the organization, the composition of the assets, and owners’ equity at any given time. In this regard, a problem turns up in submitting existing accounting information to the relevant consumers in those formats which are necessary for each of them. To make this information accessible each consumer should be prepared for its perception and use in managerial decision-making to the extent necessary. To achieve this objective in the course of the study a task was formulated: to describe the current status and features of strategic management accounting formation in the world practice and in the Republic of Kazakhstan; to justify the objective prerequisites for the formation of management accounting elements, by systematizing development stages of organizational and methodological foundations of its functioning.